Review Studi Konfigurasi Rangkaian Piezoelektrik (Seri vs Paralel) dalam Pemanenan Energi Hujan - Reyhan Martin Firnanda; Rifky (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
This study aims to examine the effect of series and parallel piezoelectric circuit configurations on the system's ability to deliver greater current and better power stability. The objective of the study is to obtain greater electrical power from series and parallel circuits. This research method is carried out by comparing series and parallel circuits on a number of piezoelectrics that will produce voltage and electric current. Data processing will obtain electrical power and the efficiency of the mechanical energy conversion system into electricity, in this case the piezoelectric. The results found that the type of piezoelectric circuit affects electrical power and efficiency. This shows that the use of piezoelectrics as an energy harvesting device can be an alternative solution for producing small-scale, environmentally friendly electrical energy.